Pillars of the entrance porch of the Triple-shrine Temple - Temples of India Project Team (Jio Institute, 2024)
Pillars of the entrance porch of the Triple-shrine Temple are visible here. The three shrines are connected by a rectangular porch which has two types of pillars: one has a fluted shaft and the other has a square shaft. The square shaft variety is similar to the reused pillars in the mandapa (pillared hall) of the matha (monastic or residential building) in the Mahanaleshwar temple complex.